Spacing Effects on the Growth and Carbon Storage of Plantation-grown Trees in the Njala University Tree- Spacing Experimental Plots, Southern Sierra Leone - Aruna Kainyande; Alie Kamara; Stephen B. Mattia (Emerging Issues in Agricultural Sciences Vol. 1, 2023)
This study compared the growth and carbon storage of Tectona grandis, Gmelina arborea, and Terminalia ivorensis planted at four different spacings in the five-year-old spacing trial plots at Njala University; Southern Province, Sierra Leone. The spacings adopted were 1.8 m x 1.8 m, 2 m x 2 m, 3 m x 3 m, and 4 m x 4 m. The study assessed the effects of these spacings on tree growth parameters and carbon storage in the above-ground tree biomass. The species were planted in square plots consisting of four different spacings. Data was collected on tree height, diameter at breast height, and crown width. The data were subjected to analysis of variance (ANOVA) to determine significant differences in tree growth and carbon storage under different spacing levels at P < 0.05. Results revealed that spacing had a statistically significant effect on basal area per hectare (P = 0.001) and crown width (P = 0.001), with the exceptions of total tree height (P = 0.354), diameter at breast height (P = 0.234), stand volume (P = 0.131), biomass (P = 0.114) and biomass carbon (P = 0.114). The results portrayed the 1.8 m x 1.8 m spacing to lead in terms of total tree height (3.4 m) and basal area per hectare (2.15 m2 ha-1). The 2 m x 2 m gave the best results for diameter at breast height (9.18 cm) and stand volume increment (5.29 m3 ha-1), while biomass (26.4 kg) and biomass carbon (11.86 kg C) were highest in the 3 m x 3 m spacing. The widest spacing 4 m x 4 m dominated in terms of crown width increment (4.776 m). The results suggest the choice of spacing as a key determinant in achieving the intended management objectives of plantation establishment.